Strukturne značilnosti in delovanje nekaterih peptidnih antibiotikov - Bavec, Aljoša (Medicinski razgledi, 2001)
Peptide antibiotics are a very heterogenic group of antibiotics. Among them wediffer cyclic, linear, non-substituted or substituted peptide antibiotics. The main feature of almost all peptide antibiotics is their amphiphilicity. Primary structure of linear peptide antibiotics is defined as the covalent backbone structure of polypeptide chains, including the sequence of amino acidresidues. The predominant structure of long length antibiotic peptides in an aqueous medium is the helical structure called alpha helix. Short length monomer peptides have very little secondary structure and exist mainly as a random coil. A typical amphipathic alpha helix is characterized by a flat hydrophobic and hydrophilic face along the axe of the molecule that interacts with polar and non-polar surfaces, like phospholipid bilayers, by packing around them in rigid, well-ordered, alpha helical arrangements. Cyclic peptideantibiotics show little potency for alpha helical conformation since they adopt bulky non-peptide groups. Rather, they express polar and non-polar regions that alternate with each other, form 'leafs' that resemble on beta sheets. Knowledge about structural characteristics of peptide antibiotics is very important for the development of new class of highly efficient antibioticdrugs.
Keywords: Antibiotics, peptide; Antibiotiki peptidni; Pharmacology; Struktura-aktivnost, razmerje; farmakologija; Structure-activity relationship; antibiotic; antibiotiki; delovanje; biokemija